Let be the sequence defined as . Compute .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
This is a slightly simpler version of this problem .
In particular, all we need to show is that 0 ≤ n ! e − ⌊ n ! e ⌋ = k = n + 1 ∑ ∞ k ! n ! ≤ k = 1 ∑ ∞ ( n + 1 ) k 1 = n 1 n → ∞ 0 as then n → ∞ lim sin ( 2 π n ! e ) = n → ∞ lim sin ( 2 π ( n ! e − ⌊ n ! e ⌋ ) ) = sin ( 0 ) = 0